(untitled) (Global Journals of Research in Engineering, 2022)
Optimization initiatives generally include leveraging technologies and optimizing existing network systems for the purpose of quality of service QoS implementation redundant data elimination data compression improved application delivery traffic shaping to reduce packet loss This article aims to meet the requirements by on-site engineers on solving handover and call drop problems The challenges faced by telecommunications companies remains a menace and a huge problem for the Gambia and the world at large The researchers have done some tremendous work in this branch of wireless communications unfortunately it still remains unraveled Relatively handover is closely very linked to call drop Handover failure probably leads to call drop and therefore handover-caused call drop is arranged in handover success rate optimization This paper describes the methods for evaluating network handover and call drop performance testing and troubleshooting methods